A systematic review of comparative efficacy of treatments and controls for depression. - Arif Khan; James Faucett; Pesach Lichtenberg; Irving Kirsch; Walter A Brown (PLoS ONE, 2012)
Background Although previous meta-analyses have examined effects of antidepressants, psychotherapy, and alternative therapies for depression, the efficacy of these treatments alone and in combination has not been systematically compared. We hypothesized that the differences between approved depression treatments and controls would be small. Methods and findings The authors first reviewed data from Food and Drug Administration Summary Basis of Approval reports of 62 pivotal antidepressant trials consisting of data from 13,802 depressed patients. This was followed by a systematic review of data from 115 published trials evaluating efficacy of psychotherapies and alternative therapies for depression. The published depression trials consisted of 10,310 depressed patients. We assessed the percentage symptom reduction experienced by the patients based on treatment assignment. Overall, antidepressants led to greater symptom reduction compared to placebo among both unpublished FDA data and published trials (F = 38.5, df = 239, p<0.001). In the published trials we noted that the magnitude of symptom reduction with active depression treatments compared to controls was significantly larger when raters evaluating treatment effects were un-blinded compared to the trials with blinded raters (F = 2.17, df = 313, p<0.05). In the blinded trials, the combination of antidepressants and psychotherapy provided a slight advantage over antidepressants (p = 0.027) and psychotherapy (p = 0.022) alone. The magnitude of symptom reduction was greater with psychotherapies compared to placebo (p = 0.019), treatment-as-usual (p = 0.012) and waiting-list (p<0.001). Differences were not seen with psychotherapy compared to antidepressants, alternative therapies or active intervention controls. Conclusions In conclusion, the combination of psychotherapy and antidepressants for depression may provide a slight advantage whereas antidepressants alone and psychotherapy alone are not significantly different from alternative therapies or active intervention controls. These data suggest that type of treatment offered is less important than getting depressed patients involved in an active therapeutic program. Future research should consider whether certain patient profiles might justify a specific treatment modality.